Implementación de una máquina extrusora de ladrillos en la microempresa rey saúl del cantón Saquisilí - Almache Oña, Brayan Paúl (2019)
The delay in the production of bricks generated by the elaboration of the traditional product, limits the economy in the micro-enterprise of the locality, the present investigation refers to the process study of brick molding, this has as its purpose the implementation of a brick extruder machine in the "Rey Saúl" micro-enterprise, that allows to improve the elaboration time in the above mentioned process, by means of the analysis the conformed of the piece to manufacture and of the process of extrusion for the method of conceptual design, it is considered to be the design parameters of the extruder machine of bricks using the foundations of the mechanical design, having in it counts the requirements of the bricks as for dimensions and physical properties, in addition the different alternatives surrender to evaluation for the accomplishment of each one of the functions that the machine executes for the design of the mechanical components. The extruder machine implemented is that of type propeller or screw without end, in that there is executed the design of the screw, the cylinder, the system of transmission, the mouthpiece, the mechanical variables and of materials, mechanisms for those who are considered to be the parameters of forces of application, speed of the mechanisms and power. An evaluation of the costs is realized for the construction of the machine including a functional analysis of the same one where she is compared by the existing ones on the market in order to determine the costs of acquisition and the capacity of production. The implementation of the extruder machine of brick allows the reduction of time of manufacture, like that also the effort that the workers use in the task of production of the same one.